ANALISIS PERTANGGUNGJAWABAN PIDANA TENAGA MEDIS ATAS TINDAKAN MALAPRAKTIK DALAM PERSPEKTIF KUHP DAN UU NOMOR 17 TAHUN 2023 TENTANG KESEHATAN - Gunawan Widjaja (CV. ADIBA AISHA AMIRA, 2025)
This study examines the criminal liability of medical personnel for malpractice from the perspective of the Criminal Code (KUHP) and Law No. 17 of 2023 on Health. The main issue raised is the difference in approach between the general nature of the KUHP and the more specific provisions of Law No. 17 of 2023 in regulating medical negligence. This study employs a normative legal method with a comparative legal approach and case studies of court decisions. The findings reveal that the KUHP holds medical personnel liable based on general negligence without considering professional standards, whereas Law No. 17/2023 emphasizes that criminal liability must be based on violations of professional standards, service standards, operational procedures, and professional ethical codes. Additionally, Law No. 17 of 2023 prioritises mechanisms such as professional disciplinary board recommendations and mediation before criminal proceedings can proceed. As a result, Law No. 17 of 2023 is considered more effective in providing legal protection for medical personnel who act in accordance with standards and ensuring justice for patients. Harmonisation and socialisation of the two regulations remain necessary to prevent overlapping in the enforcement of medical malpractice cases in Indonesia.